2015
DOI: 10.1007/s10433-015-0352-1
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, self-efficacy, and quality of life in older Czech adults

Abstract: Despite efforts to expand global physical activity (PA) surveillance data to include both low-and high-income countries worldwide, our understanding of the relationship between PA and quality of life (QOL) in older adults from culturally diverse backgrounds is limited. We tested McAuley's social-cognitive model of the PA-QOL relationship in the cultural context of the Czech Republic, a post-communist central European country. A total of 546 older Czech adults (mean age 68 years) completed a battery of question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 44 publications
1
21
0
3
Order By: Relevance
“…For example, one study found a significant relationship between self-efficacy and academic performance (Lane, Lane & Kyprianou 2004). The relationship between self-efficacy and quality of life has also been identified in some studies (Kiaei et al 2016;Mudrak et al 2016;Yeung & Lu 2014). In another study, the positive effect of self-efficacy on postsurgical complications in lung cancer was addressed (Hoffman et al 2017).…”
Section: Discussionmentioning
confidence: 83%
“…For example, one study found a significant relationship between self-efficacy and academic performance (Lane, Lane & Kyprianou 2004). The relationship between self-efficacy and quality of life has also been identified in some studies (Kiaei et al 2016;Mudrak et al 2016;Yeung & Lu 2014). In another study, the positive effect of self-efficacy on postsurgical complications in lung cancer was addressed (Hoffman et al 2017).…”
Section: Discussionmentioning
confidence: 83%
“…We assessed the effect of self-e cacy and found it has a positive effect on quality of life at 1-, 3-, and 6-month follow-ups. Self-e cacy refers to the extent to which people believe their actions will lead to a certain outcome, which means the expectation that an individual can successfully perform a certain behaviour [43]. With the treatment's progression, patients with a high level of self-e cacy regarded con icts and di culties as a chance to improve their abilities and had greater con dence in the success of the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Age-related changes in results of 8-foot up and go in groups of women in relation to their self-evaluations of health and quality of life range of motion in the joints are, in addition to strength, the basis for performing everyday activities and participation in social life. Significant differences in the cultural and social conditions and the quality of life of older people are highlighted by Mudrak et al [13]. The authors emphasize significant differences in the quality of life and physical activity in the community of elderly people from Central Europe (post-communist countries) in comparison to seniors from Western Europe or North America.…”
Section: Discussionmentioning
confidence: 99%
“…Direct support for elderly people in undertaking physical and mental activity, developing passions, finding new interests, which is especially important with the end of professional work, can be obtained, among other places, in senior clubs and universities of the third age. As shown by numerous studies of older people actively involved in these facilities, undertaking new tasks reduces the risk of depression, reduces the feeling of loneliness, as a result of making new acquaintances, improves functioning in a social group, increases satisfaction and self-confidence, and consequently improves the quality of life of a senior citizen [4,10,12,13].…”
Section: Introductionmentioning
confidence: 99%